2014
DOI: 10.1111/jam.12649
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the overconsumption of ammonium by anammox consortia under anaerobic conditions

Abstract: This investigation will have importance to better understand the anammox process operation. The overconsumption of ammonium could be used as an indicator for fluctuations in anammox cultivation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 24 publications
1
6
0
2
Order By: Relevance
“…Thus, Rhodocyclaceae could be an unknown DAMO microorganism, but its role remains to be elucidated. Fimbriimonadaceae (7%) belongs to phylum Armatimonadetes , which was previously detected in an Anammox consortia with the overconsumption of ammonium . The pyrosequencing results are broadly supported by FISH images acquired (Figure c), which confirmed the presence of DAMO archaea, and Anammox and DAMO bacteria in the community.…”
Section: Resultssupporting
confidence: 73%
“…Thus, Rhodocyclaceae could be an unknown DAMO microorganism, but its role remains to be elucidated. Fimbriimonadaceae (7%) belongs to phylum Armatimonadetes , which was previously detected in an Anammox consortia with the overconsumption of ammonium . The pyrosequencing results are broadly supported by FISH images acquired (Figure c), which confirmed the presence of DAMO archaea, and Anammox and DAMO bacteria in the community.…”
Section: Resultssupporting
confidence: 73%
“…However, the activity of nitrite-oxidizing bacteria (NOB) is questionable because AOB outcompete NOB in an environment with limited dissolved oxygen by taking advantage of their higher affinity for dissolved oxygen [38]. Previous research described the short-term overconsumption of NH 4 + -N over NO 2 ‾-N within an ANAMMOX community caused by oxidants such as super oxides or hydroxyl radials which are released under biomass stress conditions with a low concentration of ANAMMOX bacteria [39]. In Phase I, the rapid decay of bacteria which originated from the activated sludge, which did not adapt to the strict anaerobic and chemolithoautotrophic conditions, may have facilitated the release of reactive oxidants to remove NH 4 + -N.…”
Section: Anammox Reactor Performancementioning
confidence: 99%
“…Giving special attention to the families that compose the core microbiome, we observed that the ammonia removal is significantly correlated with the Fimbriimonadaceae and Pirellulaceae families. Pirellulaceae are ammonia-oxidizing bacteria 31 , while Fimbriimonadaceae belong to the Armatinomonadetes phylum, detected in ANAMMOX (ANaerobic AMMonium OXidation) consortia 32 . The two families aforementioned are positively correlated (p < 0.001, Spearman's rank correlation coefficient = 0.495), implying that the Fimbriimonadaceae family either contains ammonia oxidizing taxons or has positive interactions with ammonia oxidizing bacteria, favouring the ammonia oxidizing processes.…”
Section: Discussionmentioning
confidence: 99%